Flexural properties of additive manufactured resin designated for interim fixed dental prosthesis: Effect of nanoparticles, build direction, and artificial aging - Rawan F. Almedarham; Zainab H. Al Dawood; Fatimah M. Alatiyyah; Sultan Akhtar; Soban Q. Khan; Ashwin C. Shetty; Mohammed M. Gad (Elsevier, 2024)
Objective: This study investigates the flexural strength and elastic modulus of three-dimension (3D) printed interim resin (ASIGA) incorporating zirconium dioxide (nano-ZrO2) and silicon dioxide (nano-SiO2) nanoparticles (NPs) with different build direction and after artificial aging. Methods: Three hundred 3D-printed specimens were used for testing. Groups were modified with nano-ZrO2 or nano-SiO2 at concentrations of 0.5 wt% or 1 wt% and an unmodified control group remained unmodified (n = 10). The bar-shaped specimens (25 × 2 × 2 mm) were printed at 0, 45, and 90 degree orientations. Flexural properties were assessed using a universal testing machine. The study employed various analyses to assess material properties and bonding. Results: The flexural strength was significantly improved (P<0.001) by the inclusion of nano-ZrO2 or nano-SiO2, with a maximum value of 61.8 ± 4.3 MPa with 1 wt% nano-ZrO2 at 45° build direction. The highest elastic modulus value observed was 998.2 ± 91.2 MPa with 0.5 wt% nano-SiO2 at 90° build direction. Build direction, NP type, and NP concentration all had a statistically significant combined effect on flexural strength and elastic modulus (P=0.003*, P=0.045), respectively. Conclusion: Incorporation of nano-SiO2 and nano-ZrO2 increased the flexural properties of the interim resin used in 3D printing. Following artificial aging, all the flexural property values in the modified groups showed minimal reduction regardless of the nanoparticle concentration, while the unmodified control group showed a significant reduction. Before and after artificial aging, samples at a 0 degree build direction had a considerably higher flexural strength, although the highest elastic modulus values were found in the 90 degree group. The findings underscore the potential of nanocomposites in strengthening interim dental restorations, offering promising advancements for clinical practice.